Co-Occurrence of Gram-Negative Rods in Patients with Hematologic Malignancy and Sinopulmonary Mucormycosis - Stephanie L. Egge; Sebastian Wurster; Sung-Yeon Cho; Ying Jiang; Dierdre B. Axell-House; William R. Miller; Dimitrios P. Kontoyiannis (Journal of Fungi, 2024)
Both Mucorales and Gram-negative rods (GNRs) commonly infect patients with hematological malignancies (HM); however, their co-occurrence is understudied. Therefore, we retrospectively reviewed the records of 63 patients with HM and proven or probable sinopulmonary mucormycosis at MD Anderson Cancer Center (Houston, Texas) from 2000–2020. Seventeen out of sixty-three reviewed patients (27.0%) had sinopulmonary co-occurrence of GNRs (most commonly Pseudomonas aeruginosa and Stenotrophomonas maltophilia) within 30 days of a positive Mucorales culture or histology demonstrating Mucorales species. Eight of seventeen co-isolations of Mucorales and GNRs were found in same-day samples. All 15 patients with GNR co-occurrence and reported antimicrobial data had received anti-Pseudomonal agents within 14 days prior to diagnosis of mucormycosis and 5/15 (33.3%) had received anti-Stenotrophomonal agents. Demographic and clinical characteristics of patients with and without GNR co-occurrence were comparable. Forty-two-day all-cause mortality was high (34.9%) and comparable in patients with (41.2%) and without (32.6%) GNR detection (p = 0.53). In summary, over a quarter of heavily immunosuppressed patients with sinopulmonary mucormycosis harbored GNRs in their respiratory tract. Although no impact on survival outcomes was seen in a background of high mortality in our relatively underpowered study, pathogenesis studies are needed to understand the mutualistic interplay of GNR and Mucorales and their influence on host responses.